Memberdayakan UMKM dan Literasi Digital Berdasarkan Kearifan Lokal Masyarakat Tengger, Gunung Bromo - Imam Nuraryo; Yosaphat Danis Murtiharso; Mas Budi Widiyo Iryanto (Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
This Community Service Program (PKM) aims to enhance digital literacy capacity and online promotion skills of Micro, Small, and Medium Enterprises (MSMEs) based on local wisdom in the Surabaya and Bromo areas, East Java, and was implemented as part of the international collaboration of KAPPIJA-21 through the National Leader Forum (NLF) and the International Youth Leadership Academy (IYLA) held on December 4–7, 2025. The main problem faced by MSME actors is the relatively low ability to utilize digital technology and social media as effective marketing tools; therefore, this program was designed using a community empowerment approach through digital literacy training, promotional content creation workshops, and social media-based marketing assistance that integrates local wisdom values. The implementation methods included preliminary observation to identify partners’ needs, interactive training and workshops, field assistance (community mentoring), and evaluation through surveys and assessment of participants’ practical outputs. The results indicate an improvement in participants’ understanding and skills in using social media, creating promotional content in the form of product photos and videos, and developing more effective digital marketing strategies, while also strengthening collaborative networks among academics, students, communities, and MSME actors in supporting culture-based local economic development. Thus, this PKM program is expected to contribute to increasing the competitiveness of MSMEs and to promote sustainable digital transformation in the development of the community’s creative economy.